PENGANGKATAN ANAK BAGI ORANG TUA DITINGGAL MATI SUAMI DALAM PERSPEKTIF HUKUM ISLAM - Edi Ardiansa; Sultan, Lomba; Fajri, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2024)
This study discusses the adoption of children abandoned by their husbands from the perspective of Islamic law at the Sungguminasa Religious Court. The discussion in this study is (1) what are the legal considerations by the judge in determining the adoption of a child whose husband has died? (2) What is the review of Islamic law regarding the adoption of children by parents who have been left behind by their husbands? This research includes field research, namely qualitative field research with a research approach used is a normative-juridical approach, namely a research based on a legal provision and phenomena or events that occur in the field. Furthermore, to obtain data on this issue, the data collection methods used were interviews, documentation, library research and field research. Then, the data obtained was then analyzed and concluded. The results of this study indicate that legal considerations by judges in determining the adoption of children whose husbands have died (a case study at the Sungguminasa Religious Court), granting custody of their own children to applicants is a matter of the jurisdiction of the district court and religious court, which have been decided by the judge of the religious court based on evidence who had been asked to then be used as a basis and saw from both parties the applicant and the respondent whose child was later adopted by his own brother. The judge of the religious court refers to the rules and KHI of Islamic law to give a decision to the applicant so that the request is granted on the basis of the factor that the applicant has never been blessed with children until then her husband dies and a child is married as the heir of the family.